Pengaruh Metode Peer Education terhadap Perubahan Pengetahuan dalam Pencegahan Skabies di Pasantren Aceh Besar - Dewi Sartika (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Scabies is one of the infectious skin diseases that is still often found in Indonesia, especially in environments with high population densities such as Islamic boarding schools and orphanages. This disease is caused by an infestation of the Sarcoptes scabiei mite which causes severe itching, especially at night, so that it can interfere with the quality of sleep and daily activities of the sufferer. This condition not only has an impact on physical health, but also affects the psychological and social aspects of students. Scabies prevention efforts require adequate knowledge from each individual in order to maintain good personal hygiene and the environment. This study aims to determine the influence of health education through the peer education method on increasing students' knowledge in preventing scabies. The research method uses a quasi experiment design with a one group pre-test post-test approach. The research sample was taken using the total sampling technique, covering all students who were respondents. Data analysis was carried out by paired samples t-test to see differences in knowledge before and after the intervention. The results showed a p-value of 0.000 (<0.05) which means that there is a significant influence of the peer education method on improving student knowledge. In other words, the delivery of health information through peers is considered effective because communication takes place more intimately, is easy to accept, and is able to increase awareness of the importance of maintaining personal and environmental hygiene.